Impact of culture on the acceptance and outcomes of assessment centre method - Mohd Hanafiah, Ahmad; Mohd Rashid, Ab Hamid; Noor Azlinna, Azizan (UKM Press, Universiti Kebangsaan Malaysia, 2018)
Assessment centre (AC) is a popular method that has been used to facilitate human resource decisions and it has also been used in developing countries including Malaysia. Thus, it is important to understand how different cultural settings may influence the implementation of AC and how this might differ from its implementation in more developed nations. Therefore, this study aims to empirically investigate the impact of cultures (collectivism and relationship preference, power distance and preference hierarchy, and communication context) on the acceptance (structural aspect, information sharing, interpersonal treatment and distributive justice) and the outcomes from attending the AC (in terms of the attitude towards AC, affect and recommendation). This study utilises organisational justice theory in exploring participants’ reactions on the implementation and outcomes from attending AC. A total of thirteen hypotheses have been put forward to test the relationships amongst the culture values, acceptance and outcomes after attending the AC. The respondents for the study are from those who have had experience as participants of AC in Malaysian public sectors. In total, a survey of 405 respondents was successfully carried out and 381 useful feedbacks were analysed. Structural Equation Modelling (SEM) with SmartPLS software using Partial Least Squares (PLS) estimation is used for modelling analysis. The findings showed mixed results that would be discussed in this article. In conclusions, human resource practitioner may adopt the results from this study to improve the current practice in the selection process of staff in an organization.